Process evaluation of a randomised controlled trial aimed at improving health behaviours and vitamin D status during pregnancy: Implementation of the SPRING trial - Simone Proebstl; Christina Vogel; Wendy Lawrence; Sofia Strömmer; Hazel Inskip; Julia Hammond; Kate Hart; Karen McGill; Nicholas C. Harvey; Mary Barker; Janis Baird (PLoS ONE, 2025)
Background The Southampton PRegnancy Intervention for the Next Generation (SPRING) aimed to assess the efficacy of vitamin D supplementation and the behaviour change intervention ‘Healthy Conversation Skills’ (HCS) in improving the nutritional status of pregnant women. This paper describes the implementation of these interventions. Efficacy of HCS in improving diet quality and physical activity was evaluated in subgroups of women who discussed ways to improve these behaviours. Methods In total, 717 pregnant women were recruited from a maternity hospital in Southampton, England. Quantitative data were collected using questionnaires, case report forms, and audio recordings. Following Medical Research Council guidance, fidelity, dose, and reach were evaluated descriptively. Multiple linear regression models were produced for subgroup analyses. Results Research nurses demonstrated high competence in using HCS. Compliance with intervention protocols for delivering and receiving both interventions was high. Participants took a median of 96% of the supplements and most women (85%) attended all four Healthy Conversations sessions. Women of lower socioeconomic status and from ethnic minorities were under-represented amongst participants. Findings were not sufficient to suggest an effect of HCS on diet quality among those who discussed diet but indicated a marginally beneficial effect on physical activity among those who discussed physical activity. Results suggested a weak dose-dependent effect, with the most pronounced difference in physical activity between the control group and the intervention sub-group with the highest exposure (adjusted difference 0.16 SD (95%-CI −0.03; 0.34)). Conclusion This process evaluation confirms that the intervention components were delivered with high fidelity and rates of compliance. Altering dietary behaviours proved more challenging than altering physical activity behaviours. Research is needed to explore barriers to healthy eating faced by women during pregnancy and how these can be overcome. This paper also highlights the difficulty of engaging people from ethnic minorities and disadvantaged backgrounds in research.